Social Sustainability: Planning for Growth in Distressed Places—The German Experience in Berlin, Wittenberg, and the Ruhr - James A. Kushner (Washington University Journal of Law & Policy, 2000)
Although German plans for growth, both in the Ruhr Valley and in Berlin, have included traditional environmental and physical planning elements, they have also embraced social sustainability and the inclusion of nontraditional planning elements in their strategies for community development. These planning elements are designed to enhance the regional self image and the image that is portrayed to visitors and to instill optimism for the community’s future economic growth. Social sustainability planning involves aggressive and symbolic investments indirectly designed to enhance a community’s investment attractiveness.
Keywords: City planning and redevelopment law; Land use; Regional planning